A call for research and policy into building multi-layered social resilience toward a sustainable agricultural workforce in Switzerland - Doetzer, Julia; Kaiser-Grolimund, Andrea; Ammann, Priska; Imboden, Medea; Jeong, Ayoung; Veillat, Aline; Ingold, Karin; Winkler, Mirko S.; Fuhrimann, Samuel; Probst-Hensch, Nicole (Frontiers in Public Health, 2025)
The agricultural workforce is exposed to rapidly changing working conditions due to societal, economic, political, and ecological challenges. In the Swiss farming community, poor mental wellbeing is a growing concern and research focuses on the distribution and hazards of psychological distress in farmers and their social network. This perspective benefits from insights of the first agricultural cohort in Switzerland, illustrating the complex field that farmers operate in. Consequently, we call for a paradigm shift in research and policy from individual vulnerability to multi-layered social resilience toward building an agricultural workforce with the capacity to create pathways for a sustainable agriculture.